2020
DOI: 10.3390/app10155326
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Term Attention Networks for Skeleton-Based Action Recognition

Abstract: The same action takes different time in different cases. This difference will affect the accuracy of action recognition to a certain extent. We propose an end-to-end deep neural network called “Multi-Term Attention Networks” (MTANs), which solves the above problem by extracting temporal features with different time scales. The network consists of a Multi-Term Attention Recurrent Neural Network (MTA-RNN) and a Spatio-Temporal Convolutional Neural Network (ST-CNN). In MTA-RNN, a method for fusing multi-term temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Kinect validation, a subtask of this study, was performed in order to be sure that the Kinect system is appropriate and reliable device for medical examination rooms, orthopedic physiotherapy practices or even gyms. Most studies in the literature with Kinect-based movement tracking systems use the earlier V2 camera [34][35][36], whereas in the present study we used the completely redesigned Kinect Azure, which has an advanced Time-of-Flight depth sensor and AI algorithm to identify joint midpoints. The validation of this camera system-even if it is limited to the single-leg squat-is a valuable resource for other investigators who are experimenting with the novel capabilities of Kinect Azure in various research settings.…”
Section: Discussionmentioning
confidence: 99%
“…Kinect validation, a subtask of this study, was performed in order to be sure that the Kinect system is appropriate and reliable device for medical examination rooms, orthopedic physiotherapy practices or even gyms. Most studies in the literature with Kinect-based movement tracking systems use the earlier V2 camera [34][35][36], whereas in the present study we used the completely redesigned Kinect Azure, which has an advanced Time-of-Flight depth sensor and AI algorithm to identify joint midpoints. The validation of this camera system-even if it is limited to the single-leg squat-is a valuable resource for other investigators who are experimenting with the novel capabilities of Kinect Azure in various research settings.…”
Section: Discussionmentioning
confidence: 99%
“…They employed totally five classifiers namely (1) "LogDet divergence based metric learning with triplet constraints (LDMLT)", (2) "Bidirectional long short-term memory network (BiLSTM)", (3) "Fully convolutional network (FCN)", (4) "DTW with city block distance (DTW-CBD)", and (5) "DTW with Euclidean distance (DTW-ED)". X. Diao et al [21] suggested a new RNN model named as "Multi-term attention networks (MTANs)" for HAR from body postures. MTANs can extract the temporal features are different scales which consists of MTA-RNN and ST-CNN.…”
Section: Body Posturesmentioning
confidence: 99%